Toxicological Effects of Lead Nitrate on Biochemical Parameters of Fresh Water Fish Oreochromis niloticus: Life Sciences-Aquatic Toxicology - Sasikumar, S.; Prakash Sahaya Leon, J. (International Journal of Life Science and Pharma Research, 2022)
Freshwater systems are exposed to a variety of pollution sources, such as industrial waste, domestic sewage, agricultural disposal and mining processes. Most of the heavy metals entering into the food chain cause physiological damage for aquatic organisms. The toxicological effects of heavy metals are to non-target organisms like freshwater fishes. Lead is the most important heavy metal that causes bio accumulative toxicity in fish and other aquatic organisms. Lead nitrate is one of the heavy metals, that are found in the environment and causes many adverse effects. Oreochromis niloticus is an important species in commercial fisheries in the world. Human consumption of heavy- metal polluted water can have direct or indirect effects on human health. The present study analyzed the accumulation of heavy metals in water, fish Nile tilapia and also conducted a health risk assessment on humans. In the present study, the 96h LC50 values recorded for lead nitrate was 43ppm.The fish Oreochromis niloticus were treated for the sub lethal concentration of 1/10th,1/20/ and 1/30of lead nitrate (Pb (NO3)2) for the period of 30 days to get biochemical variations of different tissues in the Gill, Liver, Muscle and Kidney. The decreased level of Carbohydrate observed in Lead nitrate exposed fish at all the sub lethal concentrations (1/10, 1/20 and 1/30). The level of total protein and Lipid concentrations were decreased in Gill, Liver, Muscle and Kidney of lead nitrate treated fish Oreochromis niloticus. The depletion of protein, lipid, Carbohydrate content in Gill, Liver, Muscle and Kidney tissues of Oreochromis niloticus was due to the toxicant stress caused by Heavy metal Lead nitrate. A questionnaire-based dietary survey was conducted in 1000 healthy humans from the general population at various fish markets in various places of Krishnagiri district, Tamilnadu. Dietary data were collected in detail through face-to-face interview only on tilapia consumption. Intake (g) was computed. Statistical analyses were conducted using SPSS for Windows and all tests were considered significant at p< 0:05